Mediating effect of continuous improvement on the relationship between innovation and financial performance - Yasar, Neslihan Beyhan; Sezen, Bülent; Karakadilar, Ibrahim S. (Routledge Journals, Taylor & Francis Ltd, 2019)
The purpose of this study is to investigate the relationships between innovation, continuous improvement and financial performance, and especially to search for the existence of a mediating effect of continuous improvement on the relationship between innovation and financial performance. In this context, a research model and related hypotheses have been developed. In order to test the hypotheses in the research model, a field study was carried out using the computer-aided telephone interview method with 384 manufacturing firms in Turkey. Validity and reliability tests of the developed model are realised through exploratory and confirmatory factor analyses. Data have been analysed using correlation and regression analysis with structural equation model (SEM). Our study showed that the relationship between continuous improvement and innovation is significant. Furthermore, continuous improvement has a full mediating effect on the relationship between innovation and financial performance. The main implication of the study for managers is that continuous improvement and innovation are both driving force for companies.
Keywords: continuous improvement; innovation; financial performance; structural equation modelling; Turkey